VD_FINDINFO Jug / 2023 / 217 vom 25. Oktober 2022 - VD Tribunal cantonal (2022)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, MEURTRE, TENTATIVEDROIT PÉNAL, EXPULSIONDROIT PÉNAL | 22 ad 111 CP, 47 CP, 66a al. 2 CP, 10 CPP (CH)